1990
DOI: 10.1002/ange.19901021118
|View full text |Cite
|
Sign up to set email alerts
|

Organische Synthese — wohin?

Abstract: Es wird der Versuch unternommen, wichtige Entwicklungen auf dem Gebiet der Organischen Synthese in den letzten 25 Jahren zu skizzieren und in die Zukunft zu projizieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
10

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(37 citation statements)
references
References 855 publications
0
27
0
10
Order By: Relevance
“…[1] Man hat große Kunst in ihr gesehen, [2] und man hat versucht, sie als Handwerk zu etablieren. Man hat ihr ökonomische Regeln [3] verordnet und sie in logische Schemata eingepasst.…”
Section: Einführungunclassified
“…[1] Man hat große Kunst in ihr gesehen, [2] und man hat versucht, sie als Handwerk zu etablieren. Man hat ihr ökonomische Regeln [3] verordnet und sie in logische Schemata eingepasst.…”
Section: Einführungunclassified
“…Heteropolyanions and Polyacrylamide** Ce  dric R. Mayer, Vale  rie Cabuil,* Thierry Lalot, and Rene  Thouvenot Hybrid organic ± inorganic materials have received increasing attention over the last few years [1] as a result of the specific properties. This is due to a synergy between both organic and inorganic parts.…”
Section: Incorporation Of Magnetic Nanoparticles In New Hybrid Networmentioning
confidence: 99%
“…Therefore even this formal five-component reaction proceeds completely unambiguously with the formation of six CÀC bonds. [9] The reaction product is obtained as a single diastereomer and was characterized as the meso form by crystal structure analysis; the d,l-enantiomer pair could not be detected by 1 H NMR spectroscopy (500 MHz) or HPLC-MS, even in the crude product ( Figure 1). [10] A further improvement was achieved by using 1,3,5-triiodobenzene, whose reaction with 1 and methyl acrylate furnished the triple coupling triple cycloadduct 6 in 72 % yield.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the last synthesis provides a good benchmark for the maturity of a new synthetic method and in this microreview we discuss the scope and limitations of organocatalytic reactions in the synthesis of biologically important molecules. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007) century it seemed that transition metal-catalysed transformations were destined to have the most impact on this challenge, [1] but two publications on metal-free catalysis in 2000 undoubtedly called this into question. List, Lerner and Barbas showed that the simple amino acid proline (3) catalysed enantioselective cross-aldol reactions between acetone (1) and different aldehydes (Scheme 1, Equation 1), [2] while MacMillan, Ahrendt and Borths demonstrated that chiral imidazolidinium salts (7) were able to activate α,β-unsaturated aldehydes for asymmetric Diels-Alder reactions (Equation 2).…”
Section: Introductionmentioning
confidence: 97%